Super-lift converter multilevel DC/AC inverters used in solar panel energy systems - Yang, Shicong (2012)
This project presents design, simulation and hardware implementation of super-lift converter multilevel inverter. In order to maintain the output voltage at a constant level, the closed-loop control system was used with PI controller. With proper tuned PI controller, the Super-Lift converter was able to achieve the design specifications. In the multilevel inverter design, the zener diodes were used to divide the DC voltage from super-lift converter into several levels with equal voltage; with carefully designed switching circuit, the different voltage level was apply to the load at different timing with different duration. A microcontroller AN89S8253 was used for the switching signal design and the program code was written in C. The results of software simulation and hardware implementation for super-lift converter multilevel inverter are presented.